Drug history taking and the identification of drug related problems in an accident and emergency department. - Akwagyriam, I (1996)
OBJECTIVE--To determine the incidence of drug related problems that fail to be noted on casualty cards in patients subsequently admitted, and to compare medication histories as recorded by accident and emergency (A&E) senior house officers (SHOs) and a pharmacist. METHODS--An initial retrospective survey of 1459 acute inpatient admissions through A&E over a three month period was followed by a prospective study of 33 elderly patients. RESULTS--In the retrospective survey, 52 medication related problems were confirmed after examination of the medical records, of which only 16 were identified in A&E. In the prospective study, 125 currently prescribed items were identified by the pharmacist compared to 77 by A&E SHOs; 66% of the missed information was clinically relevant. Of 17 previous adverse drug reactions identified by the pharmacist only six were also recorded by the A&E officer. Only four over the counter medicines were identified by the A&E SHOs compared to 30 by the pharmacist. CONCLUSIONS--More accurate recording of drug history on casualty cards should be undertaken, particularly in respect of over the counter medication and the identification of drug related problems.